Transforming Public Services Through Agile Governance: Insights from SipTenan City of Pekalongan (Agile Governance and Innovation Measurement Journal, 2024)
Integrating agile governance principles into transforming public services is important to increase government efficiency and effectiveness. The SipTenan case study shows how agile governance principles can be applied in public services to increase community involvement, flexibility, and use of technology. This article discusses the development of the information system at SipTenan Pekalongan, which is implemented to increase the efficiency and effectiveness of monitoring processes and services to the community. Apart from that, this article also discusses the challenges faced by SipTenan in maintaining the continuity of education and the development of public welfare and health, as well as the role and challenges in developing information systems. The research results show that implementing agile governance principles in SipTenan can improves the quality of public services and government efficiency